Proposing the Importance of the "Compromise Ability" Component in the Institutional Dimension: A Study of the National Democratic Party (NasDem) - Babas, Ujang; Hidayat, Cecep (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
There is a debate about which dimension is most decisive in party institutionalization. Party institutionalization can first be seen from the increase in votes as an early indication. In the case of the 2014 to 2019 elections in Indonesia, the party that has seen the largest increase in votes is the NasDem Party, indicating that the party is the most institutionalized. This paper aims to examine the institutionalization of the NasDem Party. The method used is qualitative, by analyzing the empirical case of the NasDem Party. The result is that there is a dilemma in the debate on the concept of party institutionalization, and the stability of the NasDem Party's vote is relatively influenced by the organizational dimension, especially the strength of membership. Although the coherence of members seems problematic, the strength of members has contributed to the benefit of party votes. The "Ability to Compromise" component is important to be proposed as a prerequisite for balancing between dimensions of party institutionalization.